ANALISIS RESEPSI VIDEO TRIAL HAUL DAN UNBOXING BOBACOT TERHADAP REPRESENTASI KEPERCAYAAN DAN DAYA TARIK KONSUMEN - fatmawati, alfiana; Alfi Febriana, Annisa; Tutut; Indah, Tiara (JURNAL KOMUNITAS, 2026)
This research aim to find out how the Gen Z audience's reception of promotional video content uploaded by Bobacot on the YouTube platform. This research used a qualitative approach with a reception analysis method based on Stuart Hall's encoding/decoding theory. Data were obtained through in-depth interviews with five informants after they watched three Bobacot contents uploaded in April, May, and June 2025. The results showed that audiences gave different meanings to each content. The April content generally received a dominant hegemonic response, where the audience received the message according to the creator's intention. The May content showed a combination of dominant and negotiated hegemonic, while the June content received more negotiated to oppositional hegemonic due to doubts about the authenticity of the review and the relevance of the product. The findings suggested that audience reception of promotional content is influenced by personal experience, perceptions of the influencer, as well as the context of the product being reviewed.